Methyl formate and dimethyl ether electro-oxidation on PtPdSn catalyst supported on carbon nanotube decorated with carbon dots. (March 2022) - Kumar, V.B.; Kashyap, D.; Teller, H.; Gebru, M.G.; Gedanken, A.; Schechter, A.
Abstract: In this work, methyl formate (MF) and dimethyl ether (DME) electro-oxidation was studied on equimolar ratio PtPdSn catalyst supported on Vulcan Carbon XC-72, carbon nanotubes (CNT), and CNT–nitrogen-doped carbon dots (NCDs) composite. The ternary catalyst was synthesized by the ethylene glycol-assisted thermal reduction method and NCDs were synthesized by a hydrothermal method in the presence of CNT to form CNT-NCDs composite, in which the NCDs are incorporated onto the CNT surface. The activity of the catalyst in the oxidation of MF and DME was analyzed using cyclic voltammetry and chronoamperometry techniques. The ternary catalyst supported on CNT-NCDs composite (Pt1 Pd1 Sn1 /CNT-NCDs) showed a peak oxidation current of 75 mA/mg and 365 mA/mg for DME and MF, respectively, highest among the studied Pt1 Pd1 Sn1 /XC-72 and Pt1 Pd1 Sn1 /CNT. The onset potential of DME on Pt1 Pd1 Sn1 /CNT-NCDs catalyst shifted negatively by ∼200 mV compared to PtRu. Irrespective of the support material, the ternary catalysts showed a significant negative shift in the onset and peak potential of COad oxidation compared with commercial PtRu. The oxidation behavior of MF was studied in conjugation with its hydrolysis products methanol, formic acid, and mixed fuel (formic acid + methanol) solution, which disapproves the earlier proposed acid-catalyzed hydrolysis of MF to a significant degree during the electrochemical experiment. Hence, the CNT-NCDs supported ternary catalyst showed high catalytic activity and stability for electro-oxidation of DME and MF. Highlights: A ternary catalyst (Pt1 Pd1 Sn1 ) was developed for methyl formate and dimethyl ether oxidation. Methyl formate electro-oxidation was compared with formic acid and methanol. Carbon nanotube–nitrogen-doped carbon dots composite was examined as catalyst support. Effect of support materials on the catalytic activity was systematically compared. Significant negative shift in the onset potential of dimethyl ether and COad was observed.